The Effect of Principal Reduction on Household Distress: Evidence from Mortgage Cramdown - Cespedes, Jacelly; Parra, Carlos; Sialm, Clemens (Review of Financial Studies, 2026)
Abstract Mortgage cramdown enabled bankruptcy judges to discharge the underwater portion of a mortgage in a chapter 13 bankruptcy until the Supreme Court disallowed this practice in 1993. We investigate the impact of mortgage cramdown on household distress exploiting the random assignment of cases to judges. The impact of bankruptcy protection on foreclosures is reduced by more than half after the Supreme Court disallowed cramdown. Our results suggest that large principal reductions considerably decrease homeowners’ distress by reducing debt overhang.